Hair loss: The role of nutritional support in a comprehensive approach to hair loss treatment - Anna I. Krylova; Spartak F. Kaiumov; Maria I. Vasil’eva (Consilium Medicum)
Background. Telogen effluvium is the most common form of hair loss, which is manifested by the loss of more than 100 hairs in the telogen phase per day. There are various causes of hair loss, the main one being nutritional deficiencies, micro-, macronutrients and vitamins (zinc, iron, vitamin D, essential amino acids). Currently, there are no generally accepted clinical guidelines for the treatment of telogen effluvium, which makes it difficult to choose a therapeutic algorithm.